Credit Card Brand: Does It Matter? A Malaysian Perspective - Hui, Liew Shio (2003)
This research paper attempts to find out consumers' perception about the credit card branding in Malaysia. This paper is trying to give an overview about the credit card industry and provide some empirical evidence on the subject matters, the brand and its related matters.